MUSCULOSKELETAL SPECT-CT: A PICTORIAL REVIEW - Riaz, Saima (Journal of Ayub Medical College Abbottabad, 2016)
SPECT-CT being a hybrid imaging scanner provides molecular and anatomical imaging in one go as a one stop shop. The addition of correlative CT scan to the planar skeletal scintigraphy gives better localization of the lesion, its characterization and attenuation correction as well. We present a brief overview of our institutional experience with hybrid SPECT-CT, as an adjunct to planar skeletal scintigraphy. SPECT-CT imaging improves the diagnostic yield and specificity of planar skeletal scintigraphy. Keywords: Bone scan, planar skeletal scintigraphy, hybrid, SPECT-CT, equivocal bone lesions